Millaista yhteiskuntaa eri mediat tuottavat? - Karvonen, Erkki (Informaatiotutkimus, 2016)
This article engages in discussion on how information and communication technologies shape society and culture. These “media deterministic” insights are studied here with special interest in Marshall T. Poe’s (2011) book A History ofCommunications. Poe presents a detailed theory of media that aim to explain the impact of different forms of communication on human history. Technologies of speech, writing, print, electronic devices, and the Internet have each shaped their own kind of cultures and historical epochs. Poe formulates these media deterministic ideas as follows: Medium Attributes → Network Attributes → Social Practices and Values. Medium attributes are: Accessibility, Privacy, Fidelity, Volume, Velocity, Range, Persistence and Searchability. Each medium has different kind of bias based on these attributes and this way the medium highlights and supports some kind of communication networks, and furthermore, supports particular kind of social practices and ideologies (or values) that legitimize these practices. Poe’s insights are scrutinized and also challenged here.